Pengaruh Efikasi Diri dan Kontrak Psikologis terhadap Keterikatan Kerja pada Karyawan bagian Produksi - Rima Febrianti; Ugung Dwi Ario Wibowo (PSIMPHONI, 2022)
This study aims to determine the effect of self-efficacy and psychological contracts on job attachment in the employees of the production department. Multiple linear regression analysis technique is used to analyze the data. The subjects of this study were all employees of the production department with 55 people. Data collection is done by try out using the scale of job attachment, self-efficacy scale, and psychological contract scale. The job attachment scale has a reliability of 0.914, a self-efficacy scale has a reliability of 0.952 and a psychological contract scale has a reliability of 0.932. Based on the analysis of the data obtained, the value of Fcount = 66.210 with probability sig (p) = 0,000 (sig value (p) 0.05). Thus the hypothesis is accepted since there is an effect of self-efficacy and psychological contract simultaneously on job attachment to employees of the production department. Self-efficacy and psychological contracts make an effective contribution of 71.8% to job attachment (Rsquare = 0.718).